(untitled) (New York ; London, 1972)
This is a unique book which blends the ancient with the modern, and prescribes a program to develop and integrate the body and mind. Included is a discussion of Taoist sexual control, static and dynamic posturing, internal and external massage or kneading, meditation, respiratory exercises and acupressure.
Keywords: Y học, Trung Quốc,Trị liệu,Medicine, Chinese.,Therapeutics,Therapeutics